Lusophone-African SME internationalization: A case for born global and international joint ventures. Issue 3 (3rd July 2019) - Goncalves, Marcus; Smith, Erika Cornelius
Abstract: This study investigates the internationalization strategies of Lusophone Africa multinational enterprises (MNEs) from Angola and Mozambique, more specifically their entry mode. Information was gathered through a survey of 29 MNEs upper management respondents and subsequent face-to-face semi-structured interviews with 24 of them in their countries. The results suggest that most MNEs opted for equity-based investment strategies, mainly joint venture and mergers and acquisitions (M&A) as their preferred mode of entry when internationalizing. A significant group of them opted for e-commerce/e-business strategies and direct and indirect exports. A smaller portion of the interviewees chose Greenfield investment as a mode of entry. Many of these MNEs could be classified as born global/international new venture (INV). Finally, this study presents a conceptual framework for use in studying the entry mode choice of enterprises from Lusophone Africa frontier markets and presents research propositions for better understanding the determinants of entry mode strategies of enterprise from Angola and Mozambique.